(3GdeSDdjI GdLfGFjI ai eLGd YedjGJ fbd GdOe (B/ s - (3NGdO ehSi Jhfis; (3eCehf eMeO SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3GaQR GdJWhQ GdgGFd ai GdYde GdMOjK KhQI YdejI cHjQI ai TJi efGMi GdMjGI ef WH hYdhe (B: (3hJQJH Ydi GdKhQI GdYdejI GdcHjQI ai eLGd GdWH XghQ GdYOjO ef GdhSGFd GdYdGLjI GdeSJMOKI (B- (3hPdc cGdYdGL Yf WQjb fbd hRQGYI GdGYVGA (B- (3GdJi JYJeO eaQOGJgG Ydi eG jSJeO ef LSe GdGfSGf ef GYVGA hefJLGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B637-696s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdKhQI GdYdejIs; (3GdeSDdjI GdLfGFjIs; (3YedjGJ fbd GdOes; (3eNGWQ YedjGJ fbd GdOes; (3JMQje GdJOGhj HGdeMQeGJs; (3MGdI GdVQhQIs; (3GQcGf LQjeI GdZTs; (3fbd GdOe GdedhKs; (3GdfJjLI GdGLQGejIs; (3GdbUO GdNGUs; (3aYd GdJSees; (3UhQ GdGYJOGA Ydj SdGeI GdLSes; (3GdGjPGA GdeaVj Gdj GdehJs; (3eTcdI GdJbGOe aj LQjeg fbd GdOes; (3GdeSFhdjI GdLfGFjI Yf GdbJd hGdGUGHI GdNWCs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs